Identification of regenerating island-derived protein 3E in dogs - Peters, Laureen M.; Howard, Judith; Leeb, Tosso; Mevissen, Meike; Graf, Rolf; Reding Graf, Theresia (Frontiers in Veterinary Science, 2022)
Regenerating islet-derived protein (REG) 1A (aka pancreatic stone protein) and REG3A (aka pancreatitis-associated protein) are upregulated in humans with sepsis, pancreatitis, and gastrointestinal diseases, but little is known about this protein family in dogs. Our aim was to identify REG1 and REG3 family members in dogs. REG-family genes were computationally annotated in the canine genome and proteome, with verification of gene expression using publicly available RNA-seq data. The presence of the protein in canine pancreatic tissue and plasma was investigated with Western blot and immunohistochemistry, using anti-human REG1A and REG3A antibodies. Protein identity was confirmed with mass spectrometry. Two members of the REG3 subfamily were found in the canine genome, REG3E1 and REG3E2, both encoding for the same 176 AA protein, subsequently named REG3E. Anti-human REG3A antibodies demonstrated cross-reactivity with the canine REG3E protein in pancreas homogenates. In canine plasma, a protein band of approximately 17 kDa was apparent. Mass spectrometry confirmed this protein to be the product of the two annotated REG3E genes. Strong immunoreactivity to anti-human REG3A antibodies was found in sections of canine pancreas affected with acute pancreatitis, but it was weak in healthy pancreatic tissue. Recombinant canine REG3E protein underwent a selective trypsin digestion as described in other species. No evidence for the presence of a homolog of REG1A in dogs was found in any of the investigations. In conclusion, dogs express REG3E in the pancreas, whose role as biomarker merits further investigations. Homologs to human REG1A are not likely to exist in dogs.